Analyzing environmental heat stress under changing work conditions: A sensor‐based monitoring solution. Issue 5 (8th June 2022) - Sharma, Milap; Suri, Narendra Mohan; Kant, Suman; Alam, Md Sarfaraz
Abstract: Hot stressful work conditions impose subsequent suppressions on workers' wellbeing resulting in heat‐related morbidities, reduced productivity, and economic burden. Heat stress evaluations require costly monitoring tools that may be uneconomical while monitoring multiple locations simultaneously under the targeted workplace, especially in industrially developing countries. With recent technological advancements, sensor‐based intelligence could enable environmental heat stress monitoring at a substantially lesser price than costlier monitoring tools. In the present study, a sensor‐based approach has been utilized to develop a low‐cost data acquisition system involving widely used temperature‐humidity (THu) based indices and environmental sensors for monitoring heat stress parameters under three different work environments (i.e., indoor, outdoor, foundry). Notable variations were observed among respective work environments for the evaluated heat stress parameters. Higher heat exposures were attributable to the foundry and outdoor conditions than indoor. Based on the bivariate correlation analysis, strong associations were observed among respective indices ( p  < .01). For wet bulb globe temperature (WBGT), strong association was observed with modified discomfort index and fighter index of thermal stress ( R 2  = .979) followed by oxford index ( R 2  = .973) and discomfort index ( R 2  = .958). Australian Bureau of Metrology (ABM) WBGT approximation overestimated heat exposure values under the respective environments, indicating the approximated WBGT values monitored using THu sensor units were not wholly reliable. The absence of radiant effects and air velocity is a limiting factor in the present study. However, the proposed prototype could have additional integration capabilities w.r.t several remedial control measures like risk‐based early warning systems, automation controls, and real‐time data monitoring and analysis for multiple locations simultaneously, with potential payoffs like cost‐effectiveness and energy savings.